Dinamika Ekonomi dalam Konflik Perang: : Tafsir Ibnu Ashur tentang GhanÄ«mah dan Dampaknya pada Ekonomi Modern - Moch Zainuddin; A. Halil Thahir (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2025)
This article explores the dynamics of ghanÄ«mah, the wealth gained by Muslim armies from their enemies during warfare and its modern-day context, through the interpretive lens of Ibnu Ashur. It further explores how principles derived from ghanÄ«mah can inform contemporary economic policy, address issues of inequality and foster social solidarity after conflict. By linking historical interpretations of ghanÄ«mah to modern economic challenges, this study offers valuable insights into the potential of Islamic economic principles to contribute to a fairer global economy. This research is qualitative in nature with a descriptive-analytical approach, with the methodology used being library research, with primary sources being Ibnu Ashur's Tafsir al-Taá¸¥rÄ«r wa al-TanwÄ«r, and secondary sources including books, journals, scientific articles, and other relevant documents. GhanÄ«mah goes beyond mere material acquisition, serving as a mechanism for wealth redistribution aimed at restoring social and economic balance in the post-conflict context. Ibnu Ashur's analysis emphasizes the importance of justice and social responsibility, especially in protecting vulnerable groups such as orphans, the poor, and relatives of the Prophet Muhammad.